Development of a Hybrid Physiologically Based Pharmacokinetic Model with Drug‐Specific Scaling Factors in Rat to Improve Prediction of Human Pharmacokinetics. Issue 11 (9th September 2013) - Sayama, Hiroyuki; Komura, Hiroshi; Kogayu, Motohiro; Iwaki, Masahiro
<x xml:space="preserve">Abstract</x> Accurate prediction of pharmacokinetics (PK) in humans has been a vital part of drug discovery. The aims of this study are to verify the usefulness of scaling factors for clearance (CL) and apparent volume of distribution at the steady state (Vss) estimated from the difference between observed and predicted PK profiles in rats for human PK prediction, and to develop a novel hybrid physiologically based pharmacokinetic (PBPK) model with the two scaling factors. The human prediction accuracies for CL with in vitro–in vivo extrapolation and Vss with a tissue composition model were improved by using rat‐scaling factors. This improvement was explainable by data that the scaling factors for CL and Vss in rats were correlated with those in humans. The predictability of plasma concentration–time profiles by the hybrid PBPK model incorporating two scaling factors was compared mainly with that by the conventional PBPK model. The hybrid PBPK model yielded higher prediction accuracy for plasma concentrations than the conventional method. Furthermore, we proposed a tiered approach using the three prediction methods, including the hybrid Dedrick approach, that were previously reported (Sayama H, Komura H, Kogayu M. 2013. Drug Metab Dispos 41:498–507), taking the available information in the individual stages of drug discovery and development into consideration. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:4193–4204, 2013